The significance of life-events as contributing factors in childhood recurrent abdominal pain in an urban community in Malaysia - Boey, Christopher Chiong Meng; Goh, Khean Lee (Elsevier, 2001)
This study aimed to look at the link between childhood recurrent abdominal pain (RAP) and the presence of recent life-events in an urban community in Malaysia. School children aged from 9 to 15 years in the city of Petaling Jaya were randomly selected to fill in a questionnaire and to be interviewed. The prevalence of RAP among 1488 school children studied was 9.6 (95 confidence interval (CI), 8.18-11.25). Higher prevalences of RAP were found in children who had experienced the following life-events in the previous year: loss of a family member through death (P < .001), hospitalisation of a family member (P < .001), the child's own hospitalisation (P=.001), change of address (P < .001), change in occupation of an immediate family member (P < .001), failure in a major school examination (P < .001), bullying at school (P=.001). Following logistic regression analysis, five life-events remain significant: hospitalisation of a family member (P=.038), the child's own hospitalisation (P=.034), change in occupation of an immediate family member (P=.049), examination failure (P=.001) and bullying at school (P=.028). This study strongly suggests that recent stressful life-events are important risk-factors for RA-P. (C) 2001 Elsevier Science Inc. All rights reserved.